32 yolks : from my mother's table to working the line - Ripert, Eric (Random House, 2016)
"Before he earned his third Michelin star at his iconic restaurant, Le Bernardin, the James Beard Award for Outstanding Chef of the Year, became a regular guest judge on Bravo's Top Chef, even before he knew how to make a proper omelet, Eric Ripert was a young boy in the South of France who felt that his world had come to an end. At the age of five, his parents went through a bitter divorce. Eric moved away with his mother, whose new husband, Serge, quickly grew to resent Eric and seemed to delight in making him miserable. The only place Eric felt at home was the kitchen, where his mother tried to cheer him up with lavish meals, but once the plates had been cleared, his unhappiness returned. Then he met Jacques, a locally renowned chef and restaurant owner. Jacques took Eric under his wing, letting him into his kitchen everyday after school where he would teach Eric how to make real chocolate mousse and regale him with stories from his travels. Watching Jacques and the obvious pride he took in his work, Eric began to see a future for himself, one in which his lifelong love of food could become something that he shared with other people. His desire to not only cook but to become the best would lead him into some of the most celebrated and demanding kitchens in Paris, serving under legendary chefs like Joel Robuchon and Jean Louis Palladin and trying to survive the brutal, exacting environment of their kitchens. Like Jacques Pepin's classic memoir The Apprentice, Eric Ripert's is a coming of age story about how he learned to cook and finally found his place in the kitchen"--